Reading intervention targeting phonemic awareness and symbol imagery in children with sickle cell disease. Issue 3 (6th January 2022) - Boggs, Jacklyn; Freeman, Molly; Okhomina, Victoria I.; Kang, Guolian; Heitzer, Andrew M.; Wang, Winfred C.
Abstract: Children with sickle cell disease (SCD) frequently have diminished academic attainment and are particularly vulnerable to reading dysfunction. We explored the effectiveness of a multisensory reading intervention offered during the summer to children with SCD at our institution. Subjects with reading deficits were identified through parent report, clinical findings, or school meetings. Summer reading programs utilizing Phonemic Awareness and Symbol Imagery were provided. The Lindamood–Bell Auditory Conceptualization/Phonemic Awareness Test, Third Edition (LAC‐3), and the Symbol Imagery Test were used as pre‐ and postintervention examinations to measure progress. Fifteen students (median age 9.4 years, range 6–14 years, eight females, all African American) received the Phonemic Awareness intervention, two times a week for 6 weeks. The subjects showed statistically significant gains in standard scores derived from the LAC‐3 (mean change 7.9 points, p < .001), with associated improvements in age equivalency (AE) and grade equivalency (GE). Twenty‐nine students (median age 9 years, range 6–17 years, 13 females, all African American) participated in the Symbol Imagery reading program, also two times a week for 6 weeks. These students showed significant gains in overall standard scores (mean change 9.8 points, p < .001). Although results should be interpreted with caution due to small sample sizes, we found that summer reading clinics for children with SCD improved phonological processing and symbol imagery skills, potentially leading to substantial gains in reading capability.